Assessing strategies for implementing sustainable real estate management at Ghana Cocoa Board. - Ossei - Acheampong, Kwadwo (2021)
A thesis presented to the Department of Construction Technology and Management, College of Art and Built Environment in partial fulfillment of the requirements for the Degree of Masters of Science